A Call for Intersectional Healthcare Design Research. (January 2021) - Crocker, Sophie
The majority of patient experience research has been conducted in culturally Western contexts without controlling for cultural and demographic variation. Designers are left with little choice but to apply contextually specific and demographically neutral research to a wide range of healthcare systems, cultural contexts, and demographic conditions. It is possible that some research will transfer and generate the intended outcomes. However, it is likely much will not, and there is currently little way of knowing what does and does not work in environments outside of those where the study was conducted. Healthcare design research conducted in a variety of sociocultural conditions could help to ensure healthcare facilities are designed to best suit the sociodemographic needs of their users and support the wider public health ambitions of the health system. Health inequalities that exist within and between nations are well-known, and while the systems and structures that inform these inequalities are complex, it is likely design can play a role in ensuring these inequalities are not exacerbated by the environments in which care is provided. In other words, while healthcare designers may not be able to affect the geographies of inequality outside health facilities, they should endeavor to impact those within. It is critical that studies be repeated in a wide variety of conditions and that design decisions be openly published, shared, and discussed to create a discourse around methods, ethics, and comparative studies in the field of Intersectional Healthcare Design Research.